Behavioural regulation, causality orientations and motives for physical activity participation - Wong, Si Ying (2016)
Physical inactivity has been identified as one of the leading risks for global mortality. Working adults tend to be physically inactive because opportunities for physical play decreases as they become older. The purpose of the study, framed using the Self-Determination Theory (SDT) and its mini theories, is to examine the various motivational profiles of working adults based on their behavioral regulations, and investigate the associations of each profile to motives for participating in physical activity and causality orientations. A cluster analysis was conducted to determine if the working adults can be classified into clusters based on their behavior regulations. A multivariate analysis of variance then determined the differences between the clusters based on their motives for physical activity and causality orientations. The results have identified four clusters and suggested that autonomous profiles of behaviour regulations are highly motivated by competence, enjoyment and social reasons, which have positive relationships with autonomy orientation. The findings support past SDT research and suggestions are given to government and private organizations to promote enhancement of autonomous motivation in physical activity which will help to motivate working adults to adopt and sustain a healthy lifestyle in the long run.